Lipodisqs for eukaryote lipidomics with retention of viability: Sensitivity and resistance to Leucobacter infection linked to C.elegans cuticle composition. - Bada Juarez, J; O'Rourke, D; Judge, P; Liu, L; Hodgkin, J; Watts, A (Elsevier, 2019)
Lipodisq™ nanoparticles have been used to extract surface lipids from the cuticle of two strains (wild type, N2 and the bacteria-resistant strain, agmo-1) of the C. elegans nematode without loss of viability. The extracted lipids were characterized by thin layer chromatography and MALDI-TOF-MS. The lipid profiles differed between the two strains. The extracted lipids from the bacteria-resistant strain, agmo-1, contained ether-linked (O-alkyl chain) lipids, in contrast to the wild-type strain which contained exclusively ester- linked (O-acyl) lipids. This observation is consistent with the loss of a functional alkylglycerol monooxygenase (AGMO) in the bacterial resistant strain agmo-1. The presence and abundance of other lipid species also differs between the wild-type N2 and agmo-1 nematodes, suggesting that the agmo-1 mutant strain attempts to compensate for the increase in ether-linked lipids by modulating other lipid-synthesis pathways. Together these differences not only affect the fragility of the cuticle and the buoyancy of the worm in aqueous buffer, but also interactions with surface-adhering bacteria. The much greater chemical stability of O-alkyl, non-hydrolysable linked lipids compared with hydrolysable O-acyl linked lipids, may be the origin of the resistance of the agmo-1 strain to bacterial infection, providing a more resilient cuticle for the nematode. Additionally, we show that lipid extraction with a polymer of styrene and maleic acid (SMA) provides a viable route to lipidomics studies with minimal perturbation of the organism.